Socio-economic differences in diet, physical activity and leisure-time screen use among Scottish children in 2006 and 2010: are we closing the gap? - McNeill, Geraldine; Masson, Lindsey F; Macdiarmid, Jennie I; Craig, Leone CA; Wills, Wendy J; Bromley, Catherine (Public health nutrition, 2017)
To investigate socio-economic differences in children's diet, activity and inactivity and changes in these differences over 4 years during which new policies on food in schools were introduced. Two cross-sectional surveys in which diet was assessed by FFQ and physical activity and inactivity were assessed by interviewer-administered questionnaire. Socio-economic status was assessed by the area-based Scottish Index of Multiple Deprivation. Scotland, 2006 and 2010. Children aged 3-17 years (n 1700 in 2006, n 1906 in 2010). In both surveys there were significant linear associations between socio-economic deprivation and intakes of energy, non-milk extrinsic sugars (NMES) as a percentage of food energy, sugar-sweetened beverages, confectionery, crisps and savoury snacks and leisure-time screen use (all higher among children in more deprived areas), while intakes of fruit, fruit juice and vegetables showed the opposite trend. In 2010 children in more deprived areas engaged in more physical activity out of school than those in more affluent areas, but between 2006 and 2010 there was an overall reduction in physical activity out of school. There were also small but statistically significant overall reductions in intakes of confectionery, crisps and savoury snacks, energy and NMES and saturated fat as a percentage of food energy, but no statistically significant change in socio-economic gradients in diet or activity between the two surveys. Interventions to improve diet and physical activity in children in Scotland need to be designed so as to be effective in all socio-economic groups.